PENGARUH MOTIVASI, DISIPLIN, DAN FASILITAS TERHADAP KINERJA KARYAWAN ASURANSI JIWA BUMIPUTERA 1912 SEMARANG - Erinda Fauzia; Wahyu Hidayat; Bulan Prabawani (Universitas Diponegoro, 2014)
Motivation , discipline , and work facilities is a supporting factor for achieving high performance in order to achieve optimal business profits . If the motivation , discipline, and work facilities of business is good, the high employee performance will be achieved, and the otherwise. Related to these three variables employee of Bumiputera 1912allegedly less motivated at work, lack of discipline, and didn’t get enough working facilities. For that this riset it was shown to determine how much influence the motivation, discipline, and facilities to employee performance ofBumiputera 1912 Semarang. The type of research that used areexplanatory research, with a population at all of permanent employees who work atBumiputera 1912semarangtotaly 70 people. The sampling technique census of this study, using quantitative analysis techniques analysis that techniques used is validity test, reliability test, simple linear regression , multiple linear regression , T test and F test with SPSS 15.0 tools . From the analysis of the data showing that 16.6%of motivationvariable have a significant influence on the performance variables. Discipline variables also have a significantinfluence on the 33.0 % performance variable and variable facility also has a significant influence on the 52.9 % performance variable. And the results of the study that variable influence motivation, discipline and facilities on the performance at 60.1 %, while remaining 39.9 % is explained by other non observedvariable . Advice that can given in this research is, increase work motivation by rewarding employees for their hard work for theadvancing of this company, honored in the work environment and the ability to work to get recognition from superiors and co-workers, and improve worker discipline according to standard company. completed work orders from each of supervisor so that employee more disciplined in terms of work and provide working facilities to thecompany so employees fully at work and provide facilities a large parking area , sothe employee will be easier to working if the working facility complete and decent according to the standard corporate